Bjulleten' gosudarstvennogo kontrolja : . Vestnik gosudarstvennogo kontrolja
(1944): organ Narodnogo komissariata gosudarstvennogo kontrolja Sojuza SSSR. Since (1947) titled: Vestnik gosudarstvennogo kontrolja.